PENGARUH PENGEMBANGAN KARIR DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN TELEMARKETING PADA PT TRADISI UNTUK SEMESTA CABANG CIBUBUR JAKARTA TIMUR - Herman, Herman; Ibrahim Bali Pamungkas (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the effect of career development and work discipline on the performance of telemarketing employees at PT Tradisi Untuk Semesta, Cibubur Branch, East Jakarta, both partially and simultaneously. This research uses a quantitative method with a saturated sampling technique, resulting in a total sample of 76 respondents. Data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination, and hypothesis testing. The results show that career development has a significant effect on employee performance, with a t value of 4.585 greater than the t table value of 1.666, a simple linear regression equation of Y = 29.911 + 0.270, and a coefficient of determination of 22.1%. Work discipline also has a significant effect on employee performance, with a t value of 6.414 greater than the t table value of 1.666, a simple linear regression equation of Y = 27.677 + 0.332, and a coefficient of determination of 35.7%. Simultaneously, career development and work discipline have a significant effect on employee performance, as indicated by an F value of 70.508, which is greater than the F table value of 3.12. The resulting multiple linear regression equation is Y = 13.343 + 0.318X₁ + 0.370X₂. The correlation coefficient of 0.812 indicates a strong relationship, with a coefficient of determination of 51.7%, while the remaining 48.3% is influenced by other variables outside this study.